Description of the environment as a method of naturalistic in Giorgi Tsereteli’s , The First Step“: , This research (PHDF-21-5573) has been supported by Shota Rustaveli National Science Foundation of Georgia (SRNSFG)“ - Dzodzuashvili, Tinatini ("Intercultural Dialogues" Transactions, 2023)
Authors actively use various literary methods to convey a specific idea through a certain atmosphere, intrigue or text. One of these artistic techniques is the description of the environment, which helps the reader to become a participant in this or that action. Also, it helps the author to enrich the text with interesting details and create the desired character of the character. It should be noted that the existence of naturalism in Georgian literature is not actively discussed, nor are naturalist authors named, but Giorgi Tsereteli is one of the few who is referred to as a naturalist author by some critics. In the present study, Giorgi Tsereteli's , The First Step“ is discussed as one of the Georgian texts based on naturalistic motifs, and here, the method-environment used by the author is interesting for us. Not only the "first step" and the examples of describing the environment in it were interesting for a small research, but also the author's worldview, orientation or writing style. Not only the , The first step“ and the examples of describing the environment in it were interesting for a small research, but also the author's worldview, orientation or writing style. For this purpose, the text discusses the opinions and assessments of Giorgi Tsereteli's work by various critics. Also, as an example, extensive passages are cited as text, where the author describes a specific living environment. Description, as one of the naturalistic methods presented in Giorgi Tsereteli's work, allows us to say that , Georgian writing followed in the footsteps of European literature“.